Educational psychology practice and domestic abuse: an exploratory mixed methods web survey - Skade, Lauren Jennifer (2018)
Emerging research (Cort and Cline, 2017; Dodd, 2009; Gallagher, 2010) suggests the impact of domestic abuse (DA) on children and young people’s lives is a crucial issue for Educational Psychologists (EPs). Whilst there are a number of small scale studies exploring EP practice in this area (Gallagher, 2010; Heath, 2015) researchers are yet to explore EP practice in relation to domestic abuse on a larger scale. This research adopted a mixed method web survey design to explore EP practice at a national level. A pragmatic stance was adopted, and descriptive statistics, thematic analysis and factor analysis were utilised to explore EP practice supporting children, families and schools exposed to DA, factors supporting EP engagement in this area and EPs’ views around their unique role in relation to DA. The findings suggest EPs encounter DA within their casework to varying degrees. EPs appear to vary in their consideration of DA within case formulation, and in their exploration of DA with school staff and families. Respondents varied in their approach to exploration of DA and the indicators they utilise to prompt exploration. Factor Analysis identified EPs’ confidence in introducing DA to the conversation, whilst also ensuring a co-operative relationship exists with parents, is an important factor for EP practice. EPs reported the use of a range of interventions in response to DA; however interventions specifically focused upon DA were not widely used. EPs identified an interest in further involvement with a range of interventions and 23% of respondents reported involvement in systemic approaches around DA. Further factors perceived to be important by EPs in supporting their work in this area were: supervision and training to support EP knowledge and skills, service level policy, and the establishment of a clear role for EPs around DA. The majority of respondents felt there could be a unique role for the EP around DA, with the EPs’ facilitative role and their ability to further the psychological understanding of others identified as key themes.